Pengaruh Lokasi, Kualitas Pelayanan Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Warung Bakso Di Kecamatan Maron Dan Kecamatan Gending - Rizal, Moh Saifur; Haris, Abdul; Vidiyastutik, Elok Dwi (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to determine the influence of location, service quality and product quality on purchasing decisions. Quantitative research with causal associative relationships is the type of research used. location (X1), service quality (X2) and product quality (X3) are independent variables. Meanwhile, the purchasing decision (Y) is the dependent variable used in this research. The sample in this research was 74 customers from a total population of 740 customers. The sample used in this research was a purposive sampling technique. The temporary hypothesis test (Hypothesis) can be concluded, namely that the location variable obtained the value tcount > ttable (8.156 > 1.994) indicating that location has a significant effect on purchasing decisions, the service quality variable obtained the value tcount > ttable (2.815 > 1.994) indicating that service quality has a significant effect on purchasing decisions and product quality variables, the value obtained is tcount > ttable (9.459 > ​​1.994) indicating that product quality has a significant effect on purchasing decisions.